2016
DOI: 10.17221/8881-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Possible vertical transmission of Babesia canis canis from a bitch to her puppies: a case report

Abstract: The present study reports the possible vertical transmission of Babesia canis canis from an infected bitch to her puppies. The study concerns a bitch that had developed babesiosis in week seven of pregnancy and her litter, three puppies that exhibited symptoms of the disease in Weeks 8-9 post-partum. In all animals, the infection with protozoa was confirmed by the results of a PCR blood test. The identity of the nucleotide sequences of the amplified fragment of the gene (18S RNA) isolated from the blood of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our study demonstrates for the first time that transplacental transmission of B. microti occurs in wild, naturally-infected populations of P. leucopus and M. pennsylvanicus in Connecticut and on Block Island, RI, USA, with 74% transmission efficiency from mother to fetuses. Although studies have previously reported transplacental transmission of Babesia canis canis in canines [ 22 , 23 ], B. microti in BALB/c laboratory mice [ 24 ], and humans [ 25 , 26 ] only one other study has reported vertical transmission of B. microti occurring in naturally infected rodent populations [ 27 ]. Tolkacz and colleagues [ 27 ] reported vertical transmission of B. microti in two species of vole ( Microtus arvalis and M. oeconomus ) in Poland, finding 81% infection occurring in embryos and 90% in pups.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates for the first time that transplacental transmission of B. microti occurs in wild, naturally-infected populations of P. leucopus and M. pennsylvanicus in Connecticut and on Block Island, RI, USA, with 74% transmission efficiency from mother to fetuses. Although studies have previously reported transplacental transmission of Babesia canis canis in canines [ 22 , 23 ], B. microti in BALB/c laboratory mice [ 24 ], and humans [ 25 , 26 ] only one other study has reported vertical transmission of B. microti occurring in naturally infected rodent populations [ 27 ]. Tolkacz and colleagues [ 27 ] reported vertical transmission of B. microti in two species of vole ( Microtus arvalis and M. oeconomus ) in Poland, finding 81% infection occurring in embryos and 90% in pups.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission of B. microti has been clearly demonstrated recently in BALB/c mice in our laboratory [ 15 ], with up to 100% success, and some cases of congenital babesiosis have been reported recently in the literature in dogs [ 16 18 ]. Congenital babesiosis has been recognized also in newborn human babies in the USA [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other cases of vertical transmission of Babesia sensu stricto sp. have been reported in puppies infected with Babesia canis 6 weeks after birth and in puppies with clinical signs after 8 weeks from presumed vertical transmission of B. canis canis (Mierzejewska et al 2014; Adaszek et al 2016). Because infections of raccoons with Babesia sensu stricto were not noted until at least 2–3 weeks of age, which is within the time frame of tick-transmitted prepatent periods, it is possible that these two groups of Babesia , B. microti -like sp.…”
Section: Discussionmentioning
confidence: 99%
“…The piroplasms are an important cause of disease in humans, domestic animals and some wildlife, although most piroplasms in wildlife demonstrate low pathogenicity for their natural host (Hunfeld et al 2008; Yabsley and Shock, 2012). Most piroplasms with known life cycles use ixodid ticks as vectors (Hunfeld et al 2008) although vertical transmission has been noted as a possible alternative transmission route for some piroplasms (e.g., Babesia microti in laboratory mice and humans, Babesia gibsoni and Babesia canis canis in dogs and Babesia bovis in cows) (Yeruham et al 2003; Fukumoto et al 2005; Joseph et al 2012; Mierzejewska et al 2014; Bednarska et al 2015; Adaszek et al 2016; Costa et al 2016). In addition, fighting and intermixing of individuals’ blood has been associated with direct transmission of B. gibsoni between fighting dogs (Yeagley et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation